A rare case of concomitant acute occlusion of left main coronary artery and right coronary artery with characteristic electrocardiographic pattern - Thilina Jayasekara; Hansa Sooriyagoda; Dayananda Balasooriya; Indika Wickramatunga; Lakshman Bandara; Arulkumar Jegavanthan; Ghanamoorthi Mayurathan; Subhashini Jayawickreme; Ajith Kularatne; Thilakshi Abeysinghe (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2021)
Acute Left Main Coronary Artery (LMCA) occlusion is a rare clinical presentation which often manifests as a cardiogenic shock with worse prognosis. However the clinical outcome depends on the age of the patient, co-morbidities and the patency and dominancy of Right coronary artery. Since it supplies a large myocardial territory of left ventricle, it shows a characteristic Electrocardiographic (ECG) pattern which helps to an early diagnosis. Presence of ST elevation in aVR with ST depression of more than six leads is highly characteristic for LMCA occlusion. Here we are reporting an extremely rare case of acute concomitant occlusion of LMCA and Right coronary artery manifesting as a cardiogenic shock with ST elevation in aVR, ii, iii leads with ST depression in all other leads. Patient showed excellent clinical outcome and reversal of characteristic ECG pattern following Percutaneous Coronary Intervention (PCI) to the culprit vessels.